KOASE: Disaster Mitigation Learning Media in Elementary School - Noviana, Eddy; Kurniaman, Otang; Affendi, Nofrico (Universitas Islam Negeri Raden Intan Lampung, 2020)
Disaster mitigation learning in elementary schools is the knowledge that must be taught considering that Indonesia is a disaster-prone region. This research was aimed to design and develop KOASE comics that are appropriate to be used to understand disaster mitigation. The research method used was the 4D (Define, Design, Develop, dan Disseminate) model. The feasibility of the product assessed by expert validators was 51.13 with a fairly feasible category. The teacher’s response at the development stage obtained the score of 92.08 with a very good category and the students’ responses obtained a score of 85.87 with a very good category. Then it can be concluded that the development of KOASE comics is appropriate to be used as a medium for disaster mitigation learning. It is suggested for the next researcher is to develop comics that are more specific to one type of natural disaster so that they can explore the depth of essential material. For the teacher, this comic can be used as a source of additional reading and learning media in teaching disaster mitigation.